History of sea ice in the Arctic basin: Lessons from the past for future - I. I. Borzenkova (Лëд и снег, 2016)
The process of the sea ice formation in the Arctic Ocean is analyzed for the period of the last 65 million years, i.e. from the Paleocene to the present time. Appearance of sea ice in the high latitudes is demonstrated to be caused by the negative trend in global temperatures due to decreasing of the CO2 concentration in the ancient atmosphere. Formation of seasonal and perennial ice cover in the limited area near the Pole could take place during the mid-Neogene period, about 12–13 Ma ago. However, areas of the sea icing could be obviously changed for this time during periods of the climate warming and cooling. Permanent sea ice had been formed in the early Pleistocene, i.e. about 2.0–1.8 Ma ago only. Paleoclimatic reconstructions, based on the indirect data and modeling simulation for the Holocene optimum (10–6 ka ago) and for the Last Interglacial period (the isotopic substage in the marine cross-section 5e, about 125–127 ka ago) had shown that rising of global temperatures by 1.0–1.5 °C resulted in strong decreasing of the sea ice area, and the perennial ice cover became the seasonal one. Relatively small changes in the incoming solar radiation originating during the spring-summer time due to the orbital factors played the role of a trigger for onset of the melting process. Further on, the process could be enhanced owing to difference in the albedo between the ice cover and open water. Recently, the rapid shortening of the sea ice area is noted, and in some parts of the Arctic Ocean the area is twice cut down as compared with the normal. In 2015, the record low area of the winter sea ice was observed, and therewith the maximum of the ice area shifted to the earlier period (by 15 days) as compared with the period of 1981–2010. The winter fluctuations of the sea ice areas are as much important as the summer ones, since they are the best indicators of the present-day global warming. Thus, it can be supposed that some mechanism of replacing the perennial sea ice by the seasonal ones has been started up, that is the natural process of transition from seasonal ices to the next stage that is the ice-free Arctic. On the assumption that increasing of the CO2 concentration will continue despite the efforts to reduce emissions of greenhouse gases into the atmosphere, and the radiation forcing will approach to doubling of the CO2 content, one of the scenarios of the past can be realized now.